GRAIN PRICE IMPLIKASI HARGA GABAH TERHADAP KESEJAHTERAAN PETANI TANAMAN PANGAN DAN INFLASI - ROSALINA TINEKE KUSUMAWARDHANI; Emillia Octavia (Pusat Kajian Anggaran, 2023)
The low level of welfare of food crop farmers has the potential to threaten the availability of human resources due to the threat of commodity conversion. As a result, there is a potential for inflation due to food scarcity. Therefore, the paper aims to analyze the implications of grain prices on the welfare of food crop farmers and inflation. This research uses quantitative methods with regression models. The results show that first, harvested dry grain has positive and significant implications for farmers' welfare. While milled dry grain is not significant. Second, harvested dry grain has positive and significant implications for rice prices, but the price of milled dry grain is not significant for rice prices. Third, rice prices are able to influence the inflation rate. Therefore, the government needs to make efforts, namely, first, good management of rice storage and distribution needs to be carried out by the government so that it can maintain the stock and stability of rice prices. Second, the government should regulate the distribution of planting so that the harvest can be spread more evenly. Third, the government should increase the role of farmers as rice producers.